Comparison of methods to assess psychiatric medication adherence in methadone-maintained patients with co-occurring psychiatric disorder. (1st March 2016) - Dunn, Kelly E.; King, Van L.; Brooner, Robert K.
Highlights: Medication Event Monitoring System (MEMS) outperforms self-report in patients with opioid use and psychiatric disorder. MEMS is less impacted by baseline characteristics relative to self-report. MEMS can be customized to the participant. Abstract: Background: Adherence with psychiatric medication is a critical issue that has serious individual and public health implications. This is a secondary analysis of a large-scale clinical treatment trial of co-occurring substance use and psychiatric disorder. Method: Participants ( n = 153) who received a clinically-indicated psychiatric medication ≥30 days during the 12-month study and provided corresponding data from Medication Event Monitoring System (MEMS) and Morisky Medication Taking Adherence Scale (MMAS) self-report adherence ratings were included in the analyses. Accuracy in MEMS caps openings was customized to each participant's unique required dosing schedule. Results: Consistent with expectations, MEMS-based adherence declined slowly over time, though MMAS scores of forgetting medication remained high and did not change over the 12-month study. MEMS caps openings were not significantly impacted by any baseline or treatment level variables, whereas MMAS scores were significantly associated with younger age and presence of an Axis I disorder and antisocial personality disorder, or any cluster B diagnoses. Conclusions: Results suggest that MEMS caps may be a more objective method for monitoring adherence in patients with co-occurring substance use and psychiatric disorder relative to the MMAS self-report. Participants in this study were able to successfully use the MEMS caps for a 12-month period with <1% lost or broken caps, suggesting this comorbid population is able to use the MEMS successfully. Ultimately, these data suggest that an objective method for monitoring adherence in this treatment population yield more accurate outcomes relative to self-report.